A vastly increased chemical variety of RNA modifications containing a thioacetal structure - Dal Magro, Christina; Keller, Patrick; Jacobs, Anja; Dieterich, Christoph (Angewandte Chemie. International edition, 2018)
Recently discovered new chemical entities in RNA modifications have involved surprising functional groups that enlarge the chemical space of RNA. Using LC-MS, we found over 100 signals of RNA constituents that contained a ribose moiety in tRNAs from E. coli. Feeding experiments with variegated stable isotope labeled compounds identified 37 compounds that are new structures of RNA modifications. One structure was elucidated by deuterium exchange and high-resolution mass spectrometry. The structure of msms2i6A (2-methylthiomethylenethio-N6-isopentenyl-adenosine) was confirmed by methione-D3 feeding experiments and by synthesis of the nucleobase. The msms2i6A contains a thioacetal, shown in vitro to be biosynthetically derived from ms2i6A by the radical-SAM enzyme MiaB. This enzyme performs thiomethylation, forming ms2i6A from i6A in a first turnover. The new thioacetal is formed by a second turnover. Along with the pool of 36 new modifications, this work describes a new layer of RNA modification chemistry.